Crosstalk between Long Non-Coding RNA and Spliceosomal microRNA as a Novel Biomarker for Cancer - Maram Arafat; Ruth Sperling (Non-Coding RNA, 2023)
Non-coding RNAs (ncRNAs) play diverse roles in regulating cellular processes and have been implicated in pathological conditions, including cancer, where interactions between ncRNAs play a role. Relevant here are (i) microRNAs (miRNAs), mainly known as negative regulators of gene expression in the cytoplasm. However, identification of miRNAs in the nucleus suggested novel nuclear functions, and (ii) long non-coding RNA (lncRNA) regulates gene expression at multiple levels. The recent findings of miRNA in supraspliceosomes of human breast and cervical cancer cells revealed new candidates of lncRNA targets. Here, we highlight potential cases of crosstalk between lncRNA and supraspliceosomal miRNA expressed from the same genomic region, having complementary sequences. Through RNA:RNA base pairing, changes in the level of one partner (either miRNA or lncRNA), as occur in cancer, could affect the level of the other, which might be involved in breast and cervical cancer. An example is spliceosomal mir-7704 as a negative regulator of the oncogenic lncRNA HAGLR. Because the expression of spliceosomal miRNA is cell-type-specific, the list of cis-interacting lncRNA:spliceosomal miRNA presented here is likely just the tip of the iceberg, and such interactions are likely relevant to additional cancers. We thus highlight the potential of lncRNA:spliceosomal miRNA interactions as novel targets for cancer diagnosis and therapies.